Pengaruh Earning Per Share, Operating Cash Flow, Firm Age, dan Firm Size Terhadap Profitabilitas - Tarisya Putri Budiman; Hermanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is directed to analyze the effect of Earning Per Share (EPS), Operating Cash Flow (OCF), Firm Age, and Firm Size(TA) on Profitability(ROA) of property and real estate sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research sample consists of 85 companies selected using purposive sampling method. Multiple linear regression is applied as the analytical method in this study with the assistance of E-Views software. According to the research findings, it is known that Earning Per Share and Operating Cash Flow have a positive and significant effect on profitability, while Firm Age and Firm Size do not have a significant effect.